Kegiatan Supervisi Kepala Sekolah Dengan Teknik Group Discussion Untuk Meningkatkan Kemampuan Guru Dalam Menyusun Soal Test Diagnostik Non Kognitif Di SDN Darurejo I Plandaan Jombang - Ana Kurnia Dewi (Universitas Nusantara PGRI Kediri, 2023)
This study aims to describe the increase in teachers' abilities in compiling cognitive diagnostic tests through Principal Supervision activities using group discussion techniques at Darurejo I Plandaan Elementary School, Jombang in the 2022-2023 academic year semester I. This research was conducted at SDN Darurejo I Plandaan Jombang in semester I of the 2022-2023 school year for three months to be exact in July, August, September 2022. The research subjects were class teachers in this school, a total of 10 teachers. Methods of data collection using the method of documentation and observation. The conclusion of the results of this study is an increase in teachers' abilities in compiling cognitive diagnostic tests through Principal Supervision activities using the group discussion technique at SD Darurejo I Plandaan Jombang in the odd semester of the 2022-2023 school year by 15% of each cycle. In cycle I, the percentage of the teacher's ability to compose cognitive diagnostic tests was 75.8% in the sufficient category, then increased in cycle II to 90.8% in the very good category. In addition, the supervision activities of school principals using the group discussions technique showed that teachers' readiness to participate in activities in cycle I obtained an average percentage of 80% in the good category and increased in cycle II by 97% in the very good category.